Kampung Durian Pranan Agritourism Initiatives: An Analysis of Actor Dynamics - Yulianti, Hetri; Mulyasari, Runavia; Sushartami, Wiwik (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Developing agritourism is a useful strategy to enhance the value of the local agriculture industry. Agritourism utilises agricultural products and activities to attract tourists to rural areas. As an early stage of agritourism development, land conversion has become a supporter of attempts to create agritourism attractions. The notion of locality exists to distinguish and identify the tourism attraction area. This research focuses on durian agritourism in Padukuhan Pranan, Banjaroya Village, Kalibawang, Kulon Progo Regency, Special Region of Jogjakarta. Special attention is made to the dynamics of the local actors. Data collection was carried out using ethnographic methods through observation and in-depth interviews, for approximately three months (July-September 2023). The informants in this research were several actors involved in the development and management of Kampung Durian Pranan agritourism. The study discovered that converting the property to agritourism benefited Padukuhan Pranan by establishing the Kepranan durian as a symbol of local identity. With its central emphasis on the local populace, the Pranan Durian Village Festival serves as an outstanding instance of the substantial contributions made by community members. The collaborative efforts of local actors to effect positive change are exemplified through the festival’s design and execution, which are built upon their roles as initiators, motivators, and educators. However, it is worth noting that the reestablishment of a sustainable family farm as a means to regenerate agritourism’s sustainability has yet to transpire due to the continued dearth of interest among the younger generation in agritourism. Hence, agritourism planning needs to be designed by organising activities involving the younger generation and rebuilding family farms to create resilience and sustainability.